The assessment of executive function abilities in healthy and neurodegenerative aging—A selective literature review - Idowu, Mojitola I.; Szameitat, Andre J.; Parton, Andrew (Frontiers in Aging Neuroscience, 2024)
Numerous studies have examined executive function (EF) abilities in cognitive healthy older adults, and those living with mild cognitive impairment (MCI) and Alzheimer's disease (AD). Currently, there are no standard accepted protocols for testing specific EFs, thus researchers have used their preferred tool which leads to variability in assessments of decline in a particular ability across studies. Therefore, there is a need for guidance as to the most sensitive tests for assessing EF decline. A systemic search of most current literature published between 2000 and 2022 on EF studies assessing cognitively healthy older adults, and individuals living with MCI and AD was conducted using the databases PubMed/Medline, PsycINFO, Embase, Web of Science and Google Scholar. Emphasis was placed on the EFs dual-tasking, inhibition, shifting or switching, and working memory updating. Many tasks and their outcomes were reviewed. Of particular importance was the difference in outcomes for tasks applied to the same group of participants. These various EF assessment tools demonstrate differences in effectively identifying decline in EF ability as a result of the aging process and neurodegenerative conditions, such as MCI and AD. The review identifies a variety of factors to consider in the utilisation of particular EF tasks in particular populations, including task demand and stimuli factors, and also when comparing differing results one across studies.